BEHAVIOUR OF SOME UNMARRIED MUSLIM WOMEN ON TIKTOK IN NORTHERN NIGERIA: ISLAMIC DA’WAH AS A WAY FORWARD - Sule, Muhammad Maga; Ladan, Maryam Umar (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2023)
TikTok is a new social media site that offers a lot of features to let its users create expressive content on their own. Most of the users on this platform create indecent video content about dancing excessively and other immoral acts, particularly by women. This paper, therefore, aims at discussing the behaviour of some unmarried Muslim women on TikTok in Northern Nigeria. It was observed that the attitudes of some unmarried Muslim women on social media, especially on TikTok, are unbecoming and go against the moral teachings of Islam as it relates to social engagement. The researchers also discovered that most of the women are involved in indecent behaviours on the TikTok platform, where some of these unmarried Muslim females either in the name of becoming celebrities or advertising a brand for the public to see via videos that were uploaded to the platform thereby exposing their bodies to those who are not their Mahram to see. This study was conducted using a survey method, and data were collected through in-depth interviews. The researchers therefore, recommend that Islamic Da’wah is the only way forward to curtail such unethical behaviours among Muslims in Northern Nigeria. The study also recommended that there was an urgent need for Muslim scholars in Northern Nigeria and beyond, to intensify effort through preaches in Masjid, schools, and other public gatherings on the menace of TikTok on Muslim Ummah most importantly the Youth.